PENGARUH LETAK SARANG DAN KERAPATAN TELUR TERHADAP LAJU TETAS TELUR PENYU HIJAU (Chelonia mydas) - I Ketut Sukada (Environmental Research Center (PPLH) of Udayana University, 2009)
This research was conducted in Tanjung Benoa Village, Subdistrict of Southern Kuta, Badung Regency, Bali between February 7, and April 12, 2006. The aim of this research was to observe the length of hatchery of eggs of green turtles (Chelonia mydas) in two places. Those places were: (1) which was freely exposured to the sunlight and (2) which was not freely exposed. These two places were set up to be closely to the natural (semi natural) nesting sites where eggs eggs being put underground in different densities. Factorial Randomise Block Design was applied in this research. The first factor was the density of eggs that was 40, 50, and 60 eggs in each hole and the second factor was the location of nest, whether was or was not freely exposed to the sun light. There were 4 replicates made, so the total eggs of C. mydas utilised in this research was 1200. Result of this research indicated that the hatching rates from various mean at calm place was better than those of the other place (did not calm) – higher hatching rates 4.34% (P<0,01), shorter hatching time (day) 2.5 (P<0,01) and hatchlings were bigger in size 0.14% ( P<0,01). The density of eggs of 50 for every nest was found to be significantly better (P<0,01) compared to those of the density of 40 and 60. Temperatures in calm place and that was not calm in the morning, during the mid day and in evening were 18.1600 C, 21.660C, 19.750C and 19.660C, 30.750C, 27.330C respectively.